Pembangunan Jalan Tol Demak – Semarang, Siapa Yang Diuntungkan Dan Siapa Yang Dirugikan - Joko Purnomo Suko (PSHPM Untag Semarang, 2026)
The construction of the Semarang–Demak toll road, stretching approximately 27 km, is divided into two sections: Semarang–Sayung (10.69 km) and Sayung–Demak (16.31 km). The primary objective of this infrastructure project is to reduce traffic congestion along the northern coastal route (Pantura) that connects Semarang, Demak, and Surabaya, while simultaneously improving accessibility to tourist destinations in Demak Regency. The toll road also serves a dual function as a seawall, designed to mitigate tidal flooding (rob) in the northern coastal areas of Java. This study focuses on the impact of the project on surrounding communities, particularly with respect to income, changes in livelihoods, and socio-economic as well as environmental conditions. The findings indicate benefits such as increased mobility, accelerated flow of goods and services, and the emergence of new business opportunities. Conversely, adverse impacts are also evident, including the loss of productive land, reduced access to essential resources, and significant socio-economic transformations, coupled with the risk of environmental degradation. This research provides a comprehensive overview of the beneficiaries and the disadvantaged parties affected by the Semarang–Demak toll road as a national strategic project. The analysis is expected to serve as an evaluative reference for formulating infrastructure development policies that promote greater equity and sustainability.